A randomized prospective study comparing ultrasonic shears with electrocautery for post-operative morbidity in modified radical mastectomy - Kumar, Vivek; Siddiqui, Azaz Akhtar; Singh, Nain; Saurabh, Gyan; Ali, Shadan (International Surgery Journal, 2023)
Background: Modified radical mastectomy is commonly performed surgery for breast carcinoma. The present study was conducted to compare intra-operative and post-operative surgical outcomes by using monopolar electrocautery and ultrasonic shears in MRM. Methods: A randomized prospective study was conducted with a sample size of 60 patients who were randomized into two groups. One group underwent MRM using ultrasonic shears (Group A) and the other one using monopolar electrocautery (Group B). Intra-and post-operative outcomes were compared. Results: Group A had less intra-operative blood loss and it was statistically significant. Group A had less pain score on post op day 1 and it was statistically significant. However, Group A had less intra-operative time and less drain output but it was statistically insignificant. Group A had less post-operative complication (seroma formation, wound infection, hematoma formation and flap necrosis) compare to Group B and it was statistically significant. Group A, patient had early drain removal compare to Group B, and was statistically significantly. Conclusions: Ultrasonic shears group had significantly lesser intra-operative bleeding, lesser post operative complications, post-operative early drain removal, less post operative pain score, when compared to electrocautery group. However, the two groups had no significant difference in post-operative drain output and operative time.